EDUKASI PEDULI IKLIM UNTUK MENINGKATKAN KESADARAN GENERASI MUDA TERHADAP KETAHANAN PANGAN DAN PENCEGAHAN STUNTING DI SMAN 1 BASA AMPEK BALAI, PESISIR SELATAN - Ramadhan, Nugraha; Martinsyah, Rachmad H.; Masnarivan, Yeffi; Awalina, Rahmi; Saputra, Rizky A.; Asmadi, Yuliza; Cahyani, Fitri D.; Ihsani, Meisya S.P.; Saragih, Pamadio R. B.; Hakiki, Alfath D.; Nora, Alfiando E.; Atmadihusein, Anwar D.; Firmansyah, Rifky (Jurnal Abdi Insani, 2025)
Climate change is a global issue that has a significant impact, especially for agricultural countries such as Indonesia. The agricultural sector is highly vulnerable to changes in climate patterns, temperature, and rainfall, which affect production, food security, and community welfare. The younger generation has a strategic role in facing these challenges due to its large numbers and potential as change agents. In 2024, 31.02% of Indonesia's population will be between 15 and 29 years old. Therefore, raising climate awareness among the younger generation is crucial. This program aims to increase the understanding and capacity of the younger generation through education and climate-smart agricultural practices, including climate change mitigation and adaptation to prevent food crises and stunting. The activities were designed as Pengabdian Kepada Masyarakat Terintegrasi dengan Kegiatan Mahasiswa (PKM-TKM), involving KKN students, lecturers, practitioners, and village officials. They were carried out at SMA 1 Basa Ampek Balai, Basa Ampek Balai Tapan District, Pesisir Selatan. The solutions offered include education and mitigation practices such as converting waste into compost, tree planting, and adaptation through planting calendars and biopori infiltration pits. The activities that have been carried out have succeeded in increasing the understanding, skills, and awareness of the younger generation regarding climate change issues. Through socialization, training, and technology application, participants gained theoretical knowledge and practical experience in waste processing into compost, making biopori holes, tree planting, utilizing organic mulch, processing local foods, and fish farming in buckets (Budikdamber). This activity has positively impacted participants' capacity to face the challenges of climate change while strengthening the role of the younger generation as agents of environmental and public health change.